Associação dos benefícios de transferência direta de renda no sucesso do tratamento da tuberculose no Brasil - Oliosi, Janaína Gomes Nascimento (2017)
Introduction: Despite efforts to eliminate TB, the disease remains a major public health problem, related to poverty. This is evident in the 30 countries with the highest burden of disease in which those with higher burden have greater social inequalities. Studies show the potential of social protection programs in public health and the synergy between social protection interventions and TB control programs can be effective. Objective: To describe the sociodemographic characteristics, life habits, clinical and comorbidities and to evaluate the factors associated with the outcome of treatment of TB, among the groups of beneficiaries or not of the direct transfer of income, in seven Brazilian capitals. Methods: Prospective cohort study of patients in TB treatment in seven Brazilian capitals. The data were collected from February 2014 to April 2017. Those exposed were the patients who receive the direct transfer of income and those not exposed those who do not receive. Socio-demographic, life history, clinical and comorbid characteristics were evaluated between the groups. We performed the chi-square tests of Pearson, Fisher's Exact and Mann-Whitney. We used hierarchical logistic regression, in which the TB cure was the dependent variable and the predictor variables were analyzed in levels. The data were presented in odds ratio and 95% confidence interval. Results: There were 1,017 patients analyzed in the study, of which 834 (82.01%) were not exposed and 183 (17.99%) were exposed. The exposed group has more illiterate, more unemployed, families have lower income, more people without sewage in their homes and are more brown and black compared to those not exposed. In the hierarchical analysis, the high educational level (OR 4.79) and the age group over 60 years (OR 3.65) were associated with an increase in the success of TB treatment. There was no association between exposure and outcome of tuberculosis treatment. Conclusions: This study has the potential to contribute to the debate of social policies in TB control in Brazil. Further research is needed to assess the contribution of income transfers to other social programs in reducing unfavorable outcomes of TB treatment.